Nationalisation of Banks a symposium Government of India - Planning Commission (Planning Commission, 1969)
The nationalisation of fourteen banks is totally justified in strictly economic terms as well as in terms of the broad objectives which we have pursued and shall continue to pursue so as to ensure that the hopes and aspirations of millions of our people are not sacrificed. As early as 1954, the objective of a socialist pattern of society was adopted by Parliament. This was followed by the growth of the public sector investment which provided the basic infrastructure for further industrial development.
Publications Division, Ministry of Information and Broadcasting, Government of India